Preparation of injection moulding processing for high density polyethylene via moldflow advisor 2015 simulation - Othman, M.H.; Ibrahim, M.H.I.; Amin, S.Y.M.; Abdullah, M.S. (American Scientific Publishers, 2018)
Injection moulding simulation is one of the optimization methods which may reduce the cost due to the occurrence of defects. In order to utilise this method during the preparation of injection moulding for high density polyethylene, a processing verification through simulation and the validation through practical injection moulding needs to be conducted. In this research, Moldflow Advisor 2015 software was utilised to simulate the process while Nissei NP-7F machine was used for practical injection moulding experimentation. The criteria evaluation that was considered were filling time, time to reach ejection temperature, volumetric shrinkage, warpage, and sink marks. Through the simulation, the filling time was 3.232 seconds, the time to reach ejection temperature was 36.2 seconds, and the volumetric shrinkage was 17.69%. The warpage of 0.006 mm was also predicted in this simulation. While during practical injection moulding, the filling time was 3 seconds, the volumetric shrinkage was 16.6% and 0.07 mm warpage. Both simulation and practical results have no sink marks. Therefore, it can be concluded that the simulation process had provided a good prediction for practical injection moulding preparation. The findings of this research shall be beneficial by providing the manufacturing processing reference in related with injection moulding and high density polyethylene products.